Modernism Processing Psychoanalysis: Freud, Lawrence, Nin, Joyce - SARTOR, GENEVIEVE (Trinity College Dublin. School of English. Discipline of English, 2020)
This dissertation s focus is grounded in literary modernism s engagement with psychoanalytic theory and its therapeutic applications in the early 20th century. It examines how the ubiquity of Freud s theories at that time contributed to the compositional development of modernist texts by D.H. Lawrence, Anais Nin, and James Joyce. Modernist writing was composed in Freud s wake, and in studying the modernist text compositionally, the dissertation navigates how Lawrence, Nin, and Joyce intervened, responded to, and challenged psychoanalytic concepts in writing and over time. A distinguishing feature of this study is that, rather than concentrating on final published texts to form an analysis between theory and narrative, it focuses on how material peripheral to complete texts can foster a durational understanding of how textual process runs parallel to modernism s engagement with psychoanalysis. It examines different forms of literary media, such as notebooks, letters, journals, essays, drafts, and illustrations. A text-based approach homes in on authors who spurned psychoanalytic interpretations of their work during their lifetime or who engaged in psychoanalytic therapy at the time of writing. Through a grounded focus on the text, it argues that expanding the possibilities of paratextual analysis as a method can enhance our ability to analyse how literary texts challenge the foundations of psychoanalytic interpretation.
APPROVED
Keywords: Psychoanalysis; Literary Modernism; Comparative Literature; Literary Genetics; James Joyce; Lucia Joyce; Archival Studies; D.H. Lawrence; Anais Nin